Determinants of the Incidence of Acute Respiratory Infections (ARIs) in Children Under Five at the Getengan Community Health Center, Tana Toraja Regency - Zadrak Tombeg; Erni Yetti R; Anto J Hadi; Ahmad Safii Hasibuan; Suherman Rate; Fitri Rahma Handayani; Nayodi Permayasa (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Acute Respiratory Infections (ARIs) remain one of the main health problems among toddlers in Indonesia, including in Tana Toraja Regency. The objective of the study was to identify the determinants of the incidence of Acute Respiratory Infections (ARIs) on Toddlers at Getengan Health Center Tana Toraja Regency. Methods: The study used a cross-sectional study research design. It was conducted in January 2024. The sample of the study consisted of mothers who had toddlers aged 1-5 years and visited the Getengan Health Center about 320 toddlers. The sampling technique was carried out by using purposive sampling. Data was collected through interviews using a previously validated questionnaire. Data analysis was carried out using univariate, bivariate, and multivariate analysis. Results: The results of the study showed that maternal knowledge of Acute Respiratory Infections (ARIs), use of mosquito repellent, smoking habits in the family environment, and residential density were significant determinant factors related to the incidence of Acute Respiratory Infections (ARIs) on toddlers at Getengan Community Health Center, Tana Toraja Regency. Conclusion: The implications of the study are the need to increase maternal knowledge of Acute Respiratory Infections (ARIs), reduce excessive use of mosquito repellent, and promote an environment free of cigarette smoke and air pollution to reduce the risk of Acute Respiratory Infections (ARI) on toddlers in the region